2018
DOI: 10.1103/physrevmaterials.2.114409
|View full text |Cite
|
Sign up to set email alerts
|

Role of interstitial hydrogen in SrCoO2.5 antiferromagnetic insulator

Abstract: Hydrogen exhibits qualitatively different charge states depending on the host material, as nicely explained by the state-of-the-art impurity-state calculation. Motivated by a recent experiment [Nature 546, 124 (2017)], we show that the complex oxide SrCoO2.5 represents an interesting example, in which the interstitial H appears as a deep-level center according to the commonly-used transition level calculation, but no bound electron can be found around the impurity. Via a combination of charge difference analys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…32 Using Bader charge analysis, 43 we quantified the Bader charge around Co ions in H x SCO structures at different H concentrations and showed that the valence of Co reduces upon H insertion (Figure S3), consistent with a prior computational study. 44 Therefore, the multivalence of Co 2+/3+ accounts for the charge compensation of hydrogen insertion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…32 Using Bader charge analysis, 43 we quantified the Bader charge around Co ions in H x SCO structures at different H concentrations and showed that the valence of Co reduces upon H insertion (Figure S3), consistent with a prior computational study. 44 Therefore, the multivalence of Co 2+/3+ accounts for the charge compensation of hydrogen insertion.…”
Section: Resultsmentioning
confidence: 99%
“…This lack of the proton preference among interlayer and octahedral layers in H x SCO compared to dilute H in SCO may be caused by the increased H−H interactions and the valence change of the Co cation, which reduce the small site energy difference of less than 0.3 eV between proton sites (H1−H5) in the octahedral layer and interlayer. 44 The small energetic preference of proton sites among interlayer and octahedral layers in H x SCO is greatly beneficial for proton transport. In H x SCO, a significant fraction of proton sites in the octahedral layer and interlayer are available for proton hopping, and small energy changes during the transition of proton sublattice suggest a low energy barrier for proton migration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the compositions and neighboring layers, we can define three types of layers along [001] in bulk as L-Co (6) O, L-SrO, and L-Co (4) O, respectively, as shown in Figure 1. The L-Co (6) O and L-Co Co (4) O. Theoretically, BM-SCO has several different phases that correspond to different space groups, namely, Ima2, 11,22 Imma, 23 and Pmc2 1 . 10 According to our previous calculations, Pmc2 1 is the most stable.…”
Section: Introductionmentioning
confidence: 99%
“…9 Inside this cell, to understand the complex diffusion pathways, it is essential to define each atomic layer and important atomic sites. We denote the four-coordinated and six-coordinated Co ions as Co (4) and Co (6) , respectively. There are three types of atomic layers along the [001] direction, and we denote the layer consisting of Co (6) and O ions as L-Co (6) O, the layer consisting of Co (4) and O ions as L-Co (4) O, and the layer consisting of Sr and O ions as L-SrO.…”
Section: Introductionmentioning
confidence: 99%